Neonatal jaundice: nurses’ action against early identification (Research, Society and Development, 2021)
Neonatal jaundice is the abnormal presence of biliary pigments, which may have a physiological or pathological etiology. The treatment for jaundice is varied, the most used intervention is phototherapy, with the nursing team being responsible for preparing and welcoming the baby, guiding parents and providing the necessary care to prevent the possible consequences of this treatment. The objective was to describe the role of nurses in the early identification of neonatal jaundice and nursing care during treatment using phototherapy. It was a bibliographic review, with a descriptive and qualitative character, using the Scielo, Lilacs, BVS and BDENF databases. The existence of two types of jaundice is noteworthy, the physiological one that occurs due to the immaturity of the liver for the excretion of bilirubin when serum levels exceed 25mg/dl and the pathological one, which is not characterized only by the serum levels of bilirubin. Neonatal jaundice is a common nursing diagnosis in the first week of life of newborns and may be responsible for several readmissions requiring early and effective interventions. Early diagnosis and treatment of neonatal hyperbilirubinemia is of paramount importance for the prevention of its main complication, kernicterus. For proper treatment, maternal and neonatal history, the appearance and evolution of jaundice must be observed through a thorough physical examination of the baby and blood collection for analysis, thus ensuring a safer therapy. Finally, determine which type of hyperbilirubinemia fits and use the most efficient intervention in the treatment and prevention of jaundice.